Preparation of Photo‐Crosslinking Starch Colloidal Particles. (16th February 2020) - Zhang, Rongli; Chu, Fangwen; Hu, Yunqin; Hu, Huiling; Hu, Yulong; Liu, Huan; Huo, Chaofei; Wang, Hao
Abstract: A photo‐crosslinking cinnamic acid‐modified starch (CA‐St) copolymer is synthesized through an esterification reaction using 4‐dimethylaminopyridine and 1‐(3‐dimethylaminopropyl)‐3‐ethylcarbodiimide as catalysts. The structure of the CA‐St is confirmed by 1 H nuclear magnetic resonance and infrared spectroscopy. Using the nanoprecipitation method, the photo‐crosslinking CA‐St copolymer is aggregated into colloidal particles (CPs). The formation process and photo‐crosslinking of CA‐St CPs are evaluated in terms of size distribution, and ultraviolet and visible spectrophotometry. The scanning electron microscopy shows that the CA‐St CPs comprise spherical particles with a diameter of approximately 410 nm. This type of photo‐crosslinking CP has potential applications in nano‐ and biotechnology fields. Abstract : Photo‐crosslinking polymer colloidal particles have attracted wide attention owing to their photo‐responsive or photo‐degradable properties. Photo‐crosslinking cinnamic acid modified starch colloidal particles are prepared through a nanoprecipitation method. This type of photo‐crosslinking colloidal particle has potential applications in nano‐ and biotechnology fields.